The determinants of inward foreign direct investment in China and India - Tan, Yian Yian. (Universiti Malaysia Sarawak, 2011)
This study investigates the relationship between inward Foreign Direct Investment (FDI) in China and India and its determinants such as GDP, TRADE, and exchange rate (ER). The methods applied in this are Augmented Dickey-Fuller (ADF) test, Kwiatkowski, Phillips, Schmidt, and Shim (KPSS) test, Johansen-Juselius Cointegration test, Error Correction Model to analyze the annually data from 1980 to 2009.